ANALYSIS OF DIARRHEA MANAGEMENT IN CHILDREN UNDER TWO YEARS OLD IN INDONESIA - Atik Choirul Hidajah; Erni Astutik (Universitas Airlangga, 2023)
Background: Diarrhea in children under two is still a severe problem in Indonesia, affecting achieving SDG target 3. Providing good care will reduce the risk of death in children caused by diarrhea. Purpose: This study aimed to analyze the relationship between socio-demographic characteristics, place of residence, and access to media in mothers with children under two years old and diarrhea management in children in Indonesia. Methods: This study used secondary data from the 2017 Indonesian Health Demographic Survey (DHS) with a cross-sectional study design. Analyzed were the responses of 1,061 mothers whose children under two had diarrhea in the two weeks before the survey. Samples were taken using two-stage sampling methods. The data were analyzed by chi-square and multiple logistic regression. Multiple logistic regression was adjusted for the complex sampling designs of DHS for data analysis. Results: 59.50% of children received inappropriate treatment. Older mothers (AOR 20-24 = 2.03, 95% CI = 1.03-3.98) who lived in rural areas (AOR = 1.41, 95% CI = 1.03-1.94), had access to several media (AOR = 2.03, 95% CI = 1.01-4.10), and all media (AOR = 2.23, 95% CI = 1.07-4.64), had higher odds of having a child whose diarrhea treatment was not appropriate after controlling for other variables. Conclusion: Mothers' age, residence, and access to media have a significant relationship with inappropriate diarrhea care for their children. Therefore, interventions need to focus on women who live in rural areas and have access to the media.